Student Teachers’ Experiences on Task-Based Language Teaching: A Narrative Inquiry - Astri Hapsari; Miftah Haniful Ammar; Mohammad Izam Ghali (EDULANGUE, 2020)
Student Teacher Exchange in Southeast Asia (SEA Teacher) is a project providing opportunity for pre-service teachers from universities in Southeast Asia to have teaching experiences (practicum) in schools in other countries in Southeast Asia. This study presents the experiences of four pre-service English teachers who enrolled in SEA Teacher internship program. The participants were interviewed and the data were analyzed via thematic narrative analysis. Research credibility was enhanced through multiple data sources including interview transcript, lesson plans, and student teachers’ report. The Findings revealed that soft or weak form of task-based language teaching (TBLT) was implemented, varying from those similar to traditional presentation-practice-production (PPP) paradigm, to stronger forms, such as task-supported language teaching. Strong forms of TBLT remained unproven due to students’ linguistic challenge.